An integrated biomarker perspective on Neogene–Quaternary climatic evolution in NE Tibetan Plateau: Implications for the Asian aridification. (18th April 2016) - Peng, Tingjiang; Li, Jijun; Song, Chunhui; Guo, Benhong; Liu, Jia; Zhao, Zhijun; Zhang, Jun
Abstract: The long-term paleoclimate record in Asia and its comparison with the global climate record are of vital importance to understanding the coupling mechanisms between tectonics and climate. However, such long-term climate history in Asia revealed using the biomarker perspective has remained elusive. Here, we reconstruct the Neogene–Quaternary climatic history of the Northeastern (NE) Tibetan Plateau based on the integrated biomarker records of the Tianshui Basin and multiple published data from its surrounding localities. These comprehensive results indicate that the NE Tibetan Plateau did not have a consistent aridity trend until ∼4 Ma. Before 4 Ma, the Neogene climate was generally humid although this pattern was temporarily interrupted by two drying intervals at ∼14.5–∼12.5 and ∼10–∼6 Ma. Each of the two drying intervals and the permanent aridification trend roughly correspond to one phase of global cooling and/or uplift event of the Tibetan Plateau, highlighting the importance and complexity of tectonic–climate interactions. However, our study indicates increasing influence of tectonic uplift on the NE Tibetan Plateau climate since late Pliocene.